Shift - Bradbury, Jennifer (New York : Atheneum Books for Young Readers, 2008)
When best friends Chris and Win go on a cross country bicycle trek the summer after graduating and only one returns, the FBI wants to know what happened.
School Library Journal.
Wilson's Junior High School.
Wilson's Senior High School.
Young Adult
Keywords: Best friends -- Juvenile fiction; Bicycles -- Juvenile fiction; Friendship -- Juvenile fiction; Missing persons -- Juvenile fiction; Travel -- Juvenile fiction; Best friends -- Fiction; Bicycles and bicycling -- Fiction; Friendship -- Fiction; Missing persons -- Fiction; Travel -- Fiction; Best friends -- Fiction; Bicycles -- Fiction; Friendship -- Fiction; Missing persons -- Fiction; Travel -- Fiction